Synthetic Approaches to Gliflozins: A Comprehensive Overview - Sasikala, Ch. V. A.; Nahide, Pradip D.; Beesu, Mallesh; Biswas, Sayantan; Basu, Debjit; Achanta, Srinivas; Annapragada, Ratnamala; Bandichhor, Rakeshwar (Synthesis, 2024)
Diabetes mellitus, commonly referred to as diabetes, is a persistent medical condition that contributes to a significant global mortality rate and various associated complications in individuals. To address the needs of those diagnosed with type 2 diabetes, the pharmaceutical market offers a range of antidiabetic medications. Among these options, gliflozins stand out as highly efficacious therapeutic agents for the management of type 2 diabetes. These medications inhibit the function of sodium–glucose linked transporter (SGLT) enzymes in the kidneys, effectively halting the reabsorption of sugar and leading to a reduction in the overall glucose load within the bloodstream. This review aims at providing a comprehensive overview of the various syntheses for each of the gliflozin drugs reported in the literature and also summarizes the synthetic advancements in this area to date.1 Introduction2 Synthesis of Gliflozins2.1 Canagliflozin2.2 Dapagliflozin2.3 Ipragliflozin2.4 Empagliflozin2.5 Luseogliflozin2.6 Tofogliflozin2.7 Ertugliflozin2.8 Sotagliflozin2.9 Licogliflozin2.10 Remogliflozin2.11 Henagliflozin2.12 Bexagliflozin2.13 Janagliflozin2.14 Velagliflozin2.15 Sergliflozin Etabonate2.16 Enavogliflozin3 Conclusion
Keywords: gliflozins; diabetes mellitus; sodium–glucose co-transporters; SGLT1/2 inhibitors; synthetic methodology